An open-framework silicogermanate with 26-ring channels built from seven-coordinated (Ge,Si)10(O,OH)28 clusters. - Christensen, K; Bonneau, C; Gustafsson, M; Shi, L; Sun, J; Grins, J; Jansson, K; Sbille, I; Su, B; Zou, X (2008)
We report a new open-framework silicogermanate SU-61 containing 26-ring channels with a low framework density. It can be seen as a crystalline analogue to the mesoporous silica MCM-41. The structure is built from the assembly of (Ge,Si)10(O,OH)28 clusters. It is the first time that silicon has been successfully introduced in the Ge10 cluster in significant amounts ( approximately 21% of the tetrahedral sites). Five- and six-coordinated Ge10 clusters have previously been observed in other germanate compounds leading to either dense or open structures. In SU-61, the seven-coordinated clusters fall onto yet another underlying net, the osf net. SU-61, along with other Ge10 based frameworks, shows the versatility of the germanate system to adopt defined topologies playing on the connectivity of the clusters following the principles of net decoration and scale chemistry.